Experimental investigations on electrical discharge grinding of composite material. (2021) - Kumar Bhuyan, Basanta; Kumar, Nikhil; Kumar, Ajay; Sharma, Kartik; Verma, Vineet
Abstract: Electrical Discharge Grinding is a very complex hybrid machining process of electrical discharge machining and grinding which is suitable for machining of flat surface materials by generating the spark between the non-abrasive rotating round tool and workpiece. In this process, mechanical and thermal energies are liable for improving the material removal rate and reducing the surface roughness owing to successful flushing of working gap. In the present work, an attempt has been initiated to develop Electrical Discharge Grinding setup and parametric study of input parameters such as current and wheel rpm on output parameters like material removal rate and surface roughness while the grinding the Al-SiC-B4 C-Mg as a hybrid composite workpiece material using copper tool electrode.. During the preliminary experimentation, it shows that output parameters increase while varying the current and wheel speed.